The Influence of Hajj Repayment Savings Programs and Trust on Hajj Fee Payment Decisions (A Study on Leaders at PT. Arminareka Perdana) - Wiwi Sobarsari; Achmad Jaelani; Atik Budi Paryanti (Greenation Research & Yayasan Global Resarch National, 2026)
This study aims to analyze the influence of the Hajj Repayment Savings Program and the level of Trust on Hajj Fee Payment Decisions among Leaders at PT. Arminareka Perdana. The background of this research is the phenomenon of long Hajj waiting lists in Indonesia, which necessitates mature financial planning strategies; however, fluctuations in payment commitment at the Leader level persist. This research employs a quantitative associative approach, involving 100 respondents selected through purposive sampling. Data analysis was conducted using Multiple Linear Regression via SPSS software. The results show that, simultaneously, the Hajj Repayment Savings Program and Trust significantly influence Payment Decisions, contributing 17.8%. However, partial t-test results reveal contrasting findings: the Trust variable has a positive and significant effect (Sig. 0.000), while the Hajj Repayment Savings Program does not have a significant individual effect (Sig. 0.445). This indicates that for Leaders, trust in the company's integrity and credibility is the primary driver in financial decision-making compared to the technical savings facilities provided. The research model met normality assumptions through histogram and P-P Plot tests. This study suggests that Hajj travel organizers should focus more on strengthening transparency and relational bonds with partners to increase Hajj fee repayment commitments.